Analysis of Impact Factors on Crash Performance of High Strength 6082 Alloys Consider Extrudability and Small Modifications of the Profile Geometry. (2019) - Schiffl, A.; Schiffl, I.; Hartmann, M.; Brötz, S.; Österreicher, J.; Kühlein, W.
Abstract: The ever-increasing requirements of the automotive industry in terms of crash performance necessitate the development of high strength modifications of the EN AW-6082 alloy. High amounts of strengthening elements such as Mg, Si, Cr, Mn, and Cu can lead to poor extrudability. The present work presents a statistical method for analysing the parameters to find the greatest degree of influencing leverage on extrudability. Additionally, some results from a second method reveal an improvement in crash performance of a given profile geometry. Small modifications of the rib junction of a two-chamber profile can lead to an improvement in crash performance